Succession, Replacement, and Modification of Chicken Litter Microbiota - Kubasova, Tereza; Faldynova, Marcela; Crhanova, Magdalena; Karasova, Daniela; Zeman, Michal; Babak, Vladimir; Rychlik, Ivan (Applied and environmental microbiology, 2022)
Chickens are in constant interaction with their environment, e.g., bedding and litter, and their microbiota. However, how litter microbiota develops over time and whether bedding and litter microbiota may affect the cecal microbiota is not clear. We addressed these questions using sequencing of V3/V4 variable region of 16S rRNA genes of cecal, bedding, and litter samples from broiler breeder chicken flocks for 4 months of production. Cecal, bedding, and litter samples were populated by microbiota of distinct composition. The microbiota in the bedding material did not expand in the litter. Similarly, major species from litter microbiota did not expand in the cecum. Only cecal microbiota was found in the litter forming approximately 20% of total litter microbiota. A time-dependent development of litter microbiota was observed. Escherichia coli, Staphylococcus saprophyticus, and Weissella jogaejeotgali were characteristic of fresh litter during the first month of production. Corynebacterium casei, Lactobacillus gasseri, and Lactobacillus salivarius dominated in a 2-month-old litter, Brevibacterium, Brachybacterium, and Sphingobacterium were characteristic for 3-month-old litter, and Salinococcus, Dietzia, Yaniella, and Staphylococcus lentus were common in a 4-month-old litter. Although the development was likely determined by physicochemical conditions in the litter, it might be interesting to test some of these species for active modification of litter to improve the chicken environment and welfare. IMPORTANCE Despite intimate contact, the composition of bedding, litter, and cecal microbiota differs considerably. Species characteristic for litter microbiota at different time points of chicken production were identified thus opening the possibility for active manipulation of litter microbiota.
Keywords: mikrobiota; kur domácí; bedding; RNA ribozomální 16S; litter; antibiotic resistance; microbiota; cékum; cecum; Animals; Microbiota; zvířata; Cecum; Chickens; RNA, Ribosomal, 16S; chicken